Жерді пайдалану кезіндегі құқық бұзушылық жауапкершіліктің кейбір мəселелері (Journal of actual problems of jurisprudence, 2019)
This article deals with the legal responsibility for the land of the offense. Based on the analysis of the land legislation of the Republic of Kazakhstan, the points of view of well-known scholars of land and legal sciences conclusion of unreasonableness special allocation of land and legal responsibility.